Social and Business Innovations: Are Common Measurement Approaches Possible? - Havas, Attila (Foresight and STI Governance, 2016)
This article reviews various approaches to measuring business innovation with the aim of drawing lessons for measuring social innovations, and offers several methodological and policy conclusions. First, Innovation Union Scoreboard (IUS) indicators, in principle, could be useful in settings where the dominant mode of innovation is based on R&D activities. In practice, however, both R&D and non-R&D-based modes of innovation are important. IUS, therefore, only provides a partial picture. Social innovations can rely on R&D-based technological innovations; their essence, however, tends to be organizational, managerial, and behavioural changes. The IUS indicators do not capture these types of changes. Second, an assessment of the 81 indicators used to compile the Global Innovation Index reveals that it would not be fruitful to rely on such indicators to capture social innovations. Third, given the diversity among innovation systems, a poor performance signalled by a composite indicator does not automatically identify the area(s) necessitating the most urgent policy actions; only tailored, thorough comparative analyses can do so. Finally, analysts and policy makers need to be aware of the differences between measuring (i) social innovation activities (or efforts); (ii) the framework for social innovations (pre-requisites, available inputs, skills, norms, values, behavioural patterns, etc.); and (iii) the economic, societal, and environmental impacts of social innovations.